2018
DOI: 10.3847/1538-3881/aaf04d
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Planet from the Star in Late-Type M Dwarfs: A Case Study of TRAPPIST-1g

Abstract: The atmospheres of late M stars represent a significant challenge in the characterization of any transiting exoplanets due to the presence of strong molecular features in the stellar atmosphere. TRAPPIST-1 is an ultra-cool dwarf, host to seven transiting planets, and contains its own molecular signatures which can potentially be imprinted on planetary transit lightcurves due to inhomogeneities in the occulted stellar photosphere. We present a case study on TRAPPIST-1g, the largest planet in the system, using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
131
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(140 citation statements)
references
References 54 publications
9
131
0
Order By: Relevance
“…No prominent absorption features at near-infrared wavelengths in the transmission spectra of the atmospheres of the TRAPPIST-1 planets rule out cloud-free, hydrogen-rich atmospheres (de Wit et al 2016(de Wit et al , 2018Zhang et al 2018;Burdanov et al 2019), whereas a clear hydrogen-rich atmosphere for TRAPPIST-1 f and 1 g is still in dispute (de Wit et al 2018;Moran et al 2018;Wakeford et al 2019). Our results show that all the TRAPPIST-1 planets used to have a hydrogen-rich atmosphere of 10 −2 − 1 wt% just after disk dispersal.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…No prominent absorption features at near-infrared wavelengths in the transmission spectra of the atmospheres of the TRAPPIST-1 planets rule out cloud-free, hydrogen-rich atmospheres (de Wit et al 2016(de Wit et al , 2018Zhang et al 2018;Burdanov et al 2019), whereas a clear hydrogen-rich atmosphere for TRAPPIST-1 f and 1 g is still in dispute (de Wit et al 2018;Moran et al 2018;Wakeford et al 2019). Our results show that all the TRAPPIST-1 planets used to have a hydrogen-rich atmosphere of 10 −2 − 1 wt% just after disk dispersal.…”
Section: Discussionmentioning
confidence: 59%
“…The combined spectrum of the planets rules out cloud-free, hydrogen-dominated atmospheres, except for TRAPPIST-1 f and 1 g (de Wit et al 2018;Moran et al 2018); Wakeford et al (2019) recently suggested that a clear hydrogen-dominated atmosphere may be ruled out for TRAPPIST-1 g. Since high-altitude clouds and haze are not expected to form in hydrogen-dominated atmospheres around temperate planets (e.g. Morley et al 2015), transit spectroscopy of the TRAPPIST-1 planets suggests no atmosphere or a high-metallicity atmosphere referred to as a secondary atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…First reconnaissance observations with the Hubble Space Telescope (HST) by de Wit et al (2016Wit et al ( , 2018 showed no hint of clear H/He dominated atmospheres for the six inner planets. Further studies reassessed these findings: Moran et al (2018) supported the presence of secondary volatile-rich atmospheres for planets d, e and f using revised masses (while not entirely ruling out a cloud-free H-rich atmosphere for TRAPPIST-1 e and f) and Wakeford et al (2019) ruled out a clear solar H 2 /He dominated atmosphere for TRAPPIST-1 g.…”
Section: Introductionmentioning
confidence: 86%
“…The planets are good potential targets for atmospheric characterization with JWST (Lustig-Yaeger et al 2019;Lincowski et al 2018Lincowski et al , 2019Wunderlich et al 2019;Krissansen-Totton et al 2018; Barstow & Irwin 2016;Fauchez et al 2019b). Preliminary atmospheric prescreening was performed with HST/WFC3 and the resulting low-resolution transmission spectra acquired in the 1.1-1.7 µm spectral range made it possible to exclude clear hydrogen-dominated atmospheres for six of the seven planets (de Wit et al 2016(de Wit et al , 2018Wakeford et al 2018).…”
Section: Introductionmentioning
confidence: 99%